The Influence of Economic Literacy and Entrepreneurship Education on Business Sustainability with Entrepreneurial Commitment as a Mediating Variable - Mustari Mustari; Nur Arisah (International journal of technology and education research, 2026)
This study aims to analyze the influence of economic literacy and entrepreneurship education on the sustainability of street vendor businesses in Pinrang Regency, with entrepreneurial commitment as a mediating variable. A quantitative approach was used with data from 100 respondents analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that economic literacy and entrepreneurship education have a positive and significant influence on business sustainability, with entrepreneurial commitment strengthening the relationship. Economic literacy helps entrepreneurs in financial management, while entrepreneurship education improves skills and adaptation to business challenges. This study emphasizes the importance of economic literacy and entrepreneurship education programs oriented towards increasing entrepreneurial commitment to support the sustainability of street vendor businesses in the future.